2014
DOI: 10.4269/ajtmh.13-0057
|View full text |Cite
|
Sign up to set email alerts
|

High Prevelance of Rifampin-Monoresistant Tuberculosis: A Retrospective Analysis among Iranian Pulmonary Tuberculosis Patients

Abstract: Abstract. We determined the prevalence of rifampin-monoresistant tuberculosis (RMR-TB) in Iran. Because development of RMR-TB is not common, we also identified the major risk factors associated with RMR-TB reported from different provinces of Iran. Data for 3,020 TB patients who remained or became smear positive after two, four, six, and nine months of standard first-line chemotherapy were retrospectively analyzed. Of 3,020 patients, 1,242 patients (41.1%) were culture and DNA positive for Mycobacterium tuberc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
0
20
4
1
Order By: Relevance
“…First-line tuberculosis treatment involves four drugs, the two most effective of which are isoniazid and rifampin. Strains resistant to rifampin alone, although once considered rare, now make up a large percentage of monoresistant M. tuberculosis isolates (3,4). Moreover, resistance to both rifampin and isoniazid constitutes a clinical state of multidrug resistance, which necessitates treatment with a complicated second-line regimen that is both more toxic and less effective than standard chemotherapy (5).…”
mentioning
confidence: 99%
“…First-line tuberculosis treatment involves four drugs, the two most effective of which are isoniazid and rifampin. Strains resistant to rifampin alone, although once considered rare, now make up a large percentage of monoresistant M. tuberculosis isolates (3,4). Moreover, resistance to both rifampin and isoniazid constitutes a clinical state of multidrug resistance, which necessitates treatment with a complicated second-line regimen that is both more toxic and less effective than standard chemotherapy (5).…”
mentioning
confidence: 99%
“…The National Research Institute of Tuberculosis and Lung Disease of Iran conducted a retrospective analysis for drug resistance patterns among 47 MTB isolates from Golestan province using Multiplex PCR to detect mutations in the genes responsible for RMP and INH resistance from 2010 to 2011 and showed that 4.2% of isolates were MDR (17). This percentage seems to be overestimated because they included TB patients who remained sputum smear positive after two to nine months of standard therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A molecular analysis was performed on single colonies derived from subcultures of original isolates as previously described. 13 …”
Section: Sample Collection and Preparationmentioning
confidence: 99%